Positron Emission Tomography Imaging of Mu- and Delta-Opioid Receptor Binding in Alcohol-Dependent and Healthy Control Subjects - Weerts, Elise M.; Wand, Gary S.; Kuwabara, Hiroto; Munro, Cynthia A.; Dannals, Robert F.; Hilton, John; Frost, J. James; McCaul, Mary E. (Alcoholism, clinical and experimental research, 2011)
Background:  The endogenous opioid system plays a significant role in alcohol dependence. The goal of the current study was to investigate regional brain mu‐opioid receptor (MOR) and delta‐opioid receptor (DOR) availability in recently abstinent alcohol‐dependent and age‐matched healthy control men and women with positron emission tomography (PET) imaging. Methods:  Alcohol‐dependent subjects completed an inpatient protocol, which included medically supervised withdrawal and PET imaging on day 5 of abstinence. Control subjects completed PET imaging following an overnight stay. PET scans with the MOR‐selective ligand [11C]carfentanil (CFN) were completed in 25 alcohol‐dependent and 30 control subjects. Most of these same subjects (20 alcohol‐dependent subjects and 18 controls) also completed PET scans with the DOR‐selective ligand [11C]methylnaltrindole (MeNTL). Results:  Volumes of interest and statistical parametric mapping analyses indicated that alcohol‐dependent subjects had significantly higher [11C]CFN binding potential (BPND) than healthy controls in multiple brain regions including the ventral striatum when adjusting for age, gender, and smoking status. There was an inverse relationship between [11C]CFN BPND and craving in several brain regions in alcohol‐dependent subjects. Groups did not differ in [11C]MeNTL BPND; however, [11C]MeNTL BPND in caudate was positively correlated with recent alcohol drinking in alcohol‐dependent subjects. Conclusions:  Our observation of higher [11C]CFN BPND in alcohol‐dependent subjects can result from up‐regulation of MOR and/or reduction in endogenous opioid peptides following long‐term alcohol consumption, dependence, and/or withdrawal. Alternatively, the higher [11C]CFN BPND in alcohol‐dependent subjects may be an etiological difference that predisposed these individuals to alcohol dependence or may have developed as a result of increased exposure to childhood adversity, stress, and other environmental factors known to increase MOR. Although the direction of group differences in [11C]MeNTL BPND was similar in many brain regions, differences did not achieve statistical significance, perhaps as a result of our limited sample size. Additional research is needed to further clarify these relationships. The finding that alcohol‐dependent subjects had higher [11C]CFN BPND is consistent with a prominent role of the MOR in alcohol dependence.